HAK MINORITAS KRISTEN DI TENGAH MASYARAKAT TIMUR TENGAH: STATUS SOSIAL DAN KEBIJAKAN GEREJA - Yuangga Kurnia Yahya; Linda Sari Haryani (Religi: Jurnal Studi Agama-agama, 2018)
AbstractThis article will discuss Christian rights in the Middle East as a minority. With their number not more than 10% of the total population of the Middle East. The little existence of Christianity means nothing. Historically, Christianity in the Middle East emerged several centuries before Islam was born. Therefore, they have an emotional connection and bond with this region. On the other hand, Jesus and His followers first settled in the region of Nazareth, which is currently located in the Middle East. Through Albert Hourani's glasses, the author tries to photograph the lives of Christians in the Middle East. One of the portraits taken is the number of churches that are one of the real symbols of the existence and recognition of minority rights in the Middle East. In this discussion, the churches that became the object were churches in Jerusalem, Syria, Egypt, Lebanon, Iraq, Turkey, and Jordan who were members of the Middle East Council of Churches (MECC). This study found that Christians in the Middle East still have rights as a minority. The ups and downs faced by Christians in the Middle East did not dampen the enthusiasm and the number of Christians survived under the domination of Islam.Keywords: Christian, Middle East, Minority Right, Church, Social Status.AbstrakArtikel ini akan membahas tentang hak-hak Kristen di Timur Tengah selaku minoritas. Dengan jumlah mereka yang tidak sampai 10% dari keseluruhan penduduk Timur Tengah. Eksistensi Kristen yang sedikit tidak berarti tidak ada. Secara historis, Kristen di Timur Tengah muncul beberapa abad sebelum Islam lahir. Karenanya, mereka memiliki hubungan dan ikatan emosional dengan kawasan ini. Di sisi lain, Yesus dan para pengikutNya yang pertama bermukim di kawasan Nazaret, yang saat ini terletak di Timur Tengah. Melalui kacamata Albert Hourani, penulis mencoba memotret kehidupan umat Kristen di Timur Tengah. Salah satu potret yang diambil adalah jumlah Gereja yang menjadi salah satu simbol nyata keberadaan dan pengakuan hak-hak minoritas di Timur Tengah. Dalam pembahasan ini, gereja-gereja yang menjadi objek adalah gereja-gereja di Yerussalem, Syria, Mesir, Lebanon, Iraq, Turki, dan Yordania yang tergabung dalam Middle East Council of Churches (MECC). Penelitian ini menemukan bahwa Umat Kristen di Timur Tengah masih memiliki hak sebagai minoritas. Pasang surut gelombang yang dihadapi umat Kristen di Timur Tengah tidak menyurutkan semangat dan jumlah umat Kristen bertahan di bawah dominasi agama Islam.Kata Kunci: Kristen, Timur Tengah, Hak Minoritas, Gereja, Status Sosial